Glomerular cell crosstalk. Issue 3 (May 2016) - Lennon, Rachel; Hosawi, Salman
Abstract : Purpose of review: Glomerular filtration occurs in specialized, microscopic organelles. Each glomerulus contains unique cells and these cooperate to maintain normal filtration. Phenomenal adaptation is required for the glomerulus to respond to variable mechanical loads and this adaptation requires efficient communication between the resident cells. This review will focus on the latest discoveries related to signalling events that mediate the crosstalk between glomerular cells, and detail how disease processes can influence normal regulation. Recent findings: New data indicate that the crosstalk between glomerular cells involves an increasing number of secreted signalling ligands that act in an autocrine or paracrine fashion. Furthermore, extended roles for some of the classical signalling molecules have been described and there is emerging evidence of therapeutic strategies to manipulate cellular crosstalk. The glomerular extracellular matrix harbours many of these signalling ligands, acting as a reservoir and presenting ligands to cell surface receptors. Signals can also be transferred between cells by extracellular vesicles and this is an emerging concept in cellular crosstalk. Summary: Recent discoveries are building our understanding about glomerular cell crosstalk, and this review focuses on growth factors and signalling peptides, methods of delivery to target cells, and the potential for developing new therapies for glomerular disease.